2019
DOI: 10.1111/all.13994
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of parvalbumin to gastrointestinal digestion is required for profound and long‐lasting prophylactic oral tolerance

Abstract: Background Early introduction of food allergens into children's diet is considered as a strategy for the prevention of food allergy. The major fish allergen parvalbumin exhibits high stability against gastrointestinal digestion. We investigated whether resistance of carp parvalbumin to digestion affects oral tolerance induction. Methods Natural Cyp c 1, nCyp c 1, and a gastrointestinal digestion‐sensitive recombinant Cyp c 1 mutant, mCyp c 1, were analyzed for their ability to induce oral tolerance in a murine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
(75 reference statements)
0
16
0
Order By: Relevance
“…In this context, approaches, such as prophylactic oral tolerance induction with T-cell epitope-containing peptides have been reconsidered for allergen-specific prevention [ 72 ]. A recent study performed in murine model of fish allergy showed that prophylactic feeding with the major fish allergen parvalbumin induced tolerance point to a T-cell-mediated, tolerogenic effect [ 73 ▪ ]. However, further studies will be necessary to investigate if such an effect can also be obtained with synthetic allergen-derived peptides.…”
Section: Synthetic Hypoallergenic Peptidesmentioning
confidence: 99%
“…In this context, approaches, such as prophylactic oral tolerance induction with T-cell epitope-containing peptides have been reconsidered for allergen-specific prevention [ 72 ]. A recent study performed in murine model of fish allergy showed that prophylactic feeding with the major fish allergen parvalbumin induced tolerance point to a T-cell-mediated, tolerogenic effect [ 73 ▪ ]. However, further studies will be necessary to investigate if such an effect can also be obtained with synthetic allergen-derived peptides.…”
Section: Synthetic Hypoallergenic Peptidesmentioning
confidence: 99%
“…When the calcium-binding residues of carp parvalbumin Cyp c 1 were mutated, the structural stability of the allergen, hence its resistance to digestion, were drastically affected. 39 Unlike the natural allergen, the mutated form could not induce prophylactic tolerance in a mouse model of fish allergy. 39 Interestingly, proteins with allergenic activity were found to be relatively more abundant and stable than nonallergens in extracts from birch pollen, timothy grass, ragweed pollen, and German cockroach.…”
Section: Structural Stability Of Allergensmentioning
confidence: 96%
“…39 Unlike the natural allergen, the mutated form could not induce prophylactic tolerance in a mouse model of fish allergy. 39 Interestingly, proteins with allergenic activity were found to be relatively more abundant and stable than nonallergens in extracts from birch pollen, timothy grass, ragweed pollen, and German cockroach. 40…”
Section: Structural Stability Of Allergensmentioning
confidence: 96%
See 1 more Smart Citation
“…The apo-protein has a lower IgE-binding capacity as compared with the ion-charged molecule, concluding that important IgE epitopes are located in the ion-binding regions [47]. Parvalbumin mutants with modified EF-hand motifs feature reduced IgE-binding capacity and low stability to gastrointestinal digestion [48,49]. Otherwise, parvalbumin has great molecular stability under thermal, chemical and proteolytic conditions.…”
Section: Parvalbuminsmentioning
confidence: 99%